Proposal for a methodology for sustainable rehabilitation strategies of the existing building stock: the ponte Gêa neighborhood - Santos, Michael M. (2021)
Abstract: Having in mind the objectives of the United Nations Development Agenda 2030, which refers to the sustainable principles of a circular economy, it is urgent to improve the performance of the built environment. The existing buildings must be preserved and improved in order to reduce their environmental impact, in line with the need to revert climate change and reduce the occurrence of natural disasters. This work had as its main goal to identify and define a methodology for promoting the rehabilitation of buildings in the Ponte Gêa neighborhood, in the city of Beira, Mozambique, with an emphasis on energy efficiency, water efficiency, and construction and demolition waste management. The proposed methodology aims to create a decision support method for creating strategic measures to be implemented by considering the three specific domains—energy, water, and waste. This model allows for analyzing the expected improvement according to the action to be performed, exploring both individual and community solutions. It encompasses systems of standard supply that can reveal greater efficiency and profitability. Thus, the in-depth knowledge of the characteristics of urban space and buildings allows for establishing guidelines for the renovation process of the neighborhood.